2015
DOI: 10.4172/2376-127x.1000193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethanol and Saccharin on Fecal Microbiome in Pregnant and Non-Pregnant Mice

Abstract: Research identifying connections between the gastrointestinal flora and human health has developed at a rapid pace. Several studies link the gut microbiome to a variety of biological functions beyond the gastrointestinal tract. Changes in our diets, including the consumption of artificial sweeteners, have profound effects on the composition of the gut microbiome and can, in turn, affect brain function, glucose tolerance, and inflammation. Sweeteners are often used to encourage consumption of agents such as eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Based on non-metric multi-dimensional scaling (NMDS) analysis, no marked difference was also found in samples from different time points (Fig. 2b), which was consistent with previous studies [21, 22]. The Venn diagram (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Based on non-metric multi-dimensional scaling (NMDS) analysis, no marked difference was also found in samples from different time points (Fig. 2b), which was consistent with previous studies [21, 22]. The Venn diagram (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Sweeteners are often used to encourage the consumption of agents such as ethanol and nicotine in laboratory studies that use rodents. Labrecque et al (45) evaluated the effect of ethanol in either water or saccharin on the fecal microbiome in pregnant and nonpregnant mice. Saccharin reduced Clostridium numbers, even though the total amounts of ethanol consumed were the same for the 2 groups (45).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Non-calorie sweeteners stimulate development of intolerance to glucose through changes in the gut microflora and resulting inflammatory processes in the organs (Suez et al, 2014;Nettleton et al, 2016;Bian et al, 2017). In a study of stimulation of consumption of some substances (ethanol and nicotine) by sweeteners, experiments on mice revealed that saccharin reduced the number of microorganisms of the Clostridium genus (Labrecque et al, 2015). Fig.…”
Section: Resultsmentioning
confidence: 99%